The Effect of a Compressed High School Curriculum on University Performance - Michael Dörsam; Verena Lauber (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
A recent education reform in Germany reduced the duration of academic high school education by one year but left the curriculum, and total class time unchanged. We use a unique data set of university students to investigate the effects of this reduction in years of schooling on academic achievements at the tertiary level. By exploiting variation in the implementation of the reform across school types over time, we isolate the reform e ect from cohort, state, and school type effects. Our results suggest that the reform lowers the opportunity costs of schooling and facilitates an earlier labor market entry as we find no detrimental effects while students are one year younger on average.
Keywords: I21; H52; C21; 330; School Duration; Academic Achievement; Difference-in-Differences; Germany